Association of Serum Vitamin D with Acute Myocardial Infarction in Young Patients (≤40 Years) (Bangladesh Heart Journal, 2019)
Background: Coronary heart disease (CHD) is the leading cause of death worldwide, with acute myocardial infarction (AMI) being the most severe manifestation. Recent evidence suggests that vitamin D deficiency (moderate/severe) is an important risk factor for coronary artery disease.Objectives: Considering paucity of the literature focusing young MI, the study was planned to assess the relation of different grades of low serum vitamin D with AMI in young patients admitted in a tertiary care hospital.Methods: This Hospital based case-control study was conducted in the department of cardiology in Dhaka Medical College Hospital (DMCH) over 1-year period. Patients with acute MI in young age (≤40 years) admitted in the CCU of DMCH were approached for inclusion in the study. Total 120 subjects (60 cases and 60 controls) were studied. Patients with acute MI were considered as cases and similar number of age and sex matched apparently healthy individual were included as controls. All study population were subjected to relevant investigations and detailed history along with socio-demographic data were collected. Serum vitamin D levels were categorized as severe vitamin D deficiency as a level